(untitled) (Journal of Informatics Education and Research, 2025)
The increasing prevalence of financial scams in India has underscored the urgent need for financial awareness and ethics within Indian educational institutions. This paper analyzes the potential benefits of incorporating financial awareness courses that educate youth on recognizing fraud, understanding ethical financial practices, and promoting responsible financial behavior. As young individuals remain particularly vulnerable to deceptive schemes, a strong foundation in financial literacy can empower them to make informed decisions, avoid exploitation, and ensure financial security. By examining the current state of financial education in India and drawing comparisons with international case studies, this research highlights how financial awareness, coupled with ethics, can build resilience against fraud. Furthermore, it addresses challenges such as resource limitations, lack of standardized curricula, and cultural barriers that have impeded the widespread adoption of financial courses in Indian schools. Finally, the paper presents policy recommendations advocating for the early integration of financial awareness and ethics education, partnerships with financial institutions, and the use of digital tools to enhance accessibility. This analysis aims to provide actionable insights for fostering an ethically aware and financially responsible generation, ultimately reducing the impact of financial scams and contributing to a more secure economic environment in India.